Pemeriksaan Dampak Mengkonsumsi Minuman Beralkohol Terhadap Kadar Enzim Aspartat Aminotransferase (AST) dan Alanine Aminotransferase (ALT) - Fatmawati, Shinta; Husnah, Yeni Vidhatul; Rahmawati, Previta Zeizar (Jaringan Laboratorium Medis, 2024)
Aspartat aminotransferase (ast) and alanine aminotransferase (Alt) or which is the enzyme transaminase used liver function tests. When alcohol enters the body, a metabolism in the liver is carried out with an end result of acetydehid when an excessive dose causes liver damage. The purpose of research to determine whether or not there is a correlation between the consumption of alcohol and its blast of bank. this study is a non-experiment of quantitative experimentation with a sampling technique. The respondents in this study are 24 alcohol drinkers of NTT students in the unfortunate city. And sample analysis methods of the kinetic ifcc and the chemical analyzer clinic - the mindray analyzer. On 24 of the respondents of all sexs-men will be analyzed based on long consumption, high consumption of alcohol, and heavy drink-alcohol consumption. The research data obtained will be done in a statistical test using the Pearson correlation test. Studies conducted on alcohol drinkers for a normal ast result are 18 respondents and abnormal results of 6. Studies on alcohol drinkers for normal test levels included 19 individuals and abnormal results for 5. The Pearson correlation test between the amount of consumption between the ast consumption is 0,184 and p-value > 0.05, and the high consumption of alcohol is 0.508 and the value of p-value 0.05, and the amount of drinking is an e-0.405 and p-value 0.05. Studies between consumption length and Alt levels have found a very weak link of 0,033 and p-value > 0.05, the high consumption of alcohol is 0,426 and the value of p-value 0.05, and the high drinking relationship of weak value are = 0.315 and p-value > 0.05. The study has had a negative impact on excessive consumption of alcohol, raising levels of ast and Alt especially on high-alcohol drinkers and excessive drinking frequency.